Crítica da razão excludente : desvelando novas racionalidades a partir das pesquisas em educação especial numa perspectiva inclusiva - Guimarães, Alessandro da Silva (2014)
The aim of this thesis is to produce a hermeneutic and phenomenological reflection on the practical know-how/“savoir faire” that have been produced from research dealing with the inclusion of students with special needs in regular schools. It was intended a search of bibliographic nature which focused on the production of knowledge concerning dissertations and theses that were produced in PPGE-UFES between the years 2000 and 2010 that sought to analyze the inclusive practical know-how/“savoir faire” that have come with the inclusion of students with special needs in the “spaces-times” of regular schools. It was attempted at first describe the state of the art of such research work to later understand them in a philosophical dimension. As a result, it was concluded that these studies show deeply ambiguous and paradoxical movements, revealing a profound crisis of an excluding rationality model that is ingrained in our culture and daily life of schools. Given this background, we seek to understand, from the tracks and trails left by dissertations and theses researched, how it has been shaped other forms of rationalities which establish new ways of “teaching-learning” combined with different ways of “being-feelingknowing” the world